2004
DOI: 10.1007/s00441-004-0987-2
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue in Walker 256 tumour-induced cachexia: possible association between decreased leptin concentration and mononuclear cell infiltration

Abstract: The adipose tissue (AT) is severely affected by cachexia, a paraneoplastic syndrome, which increases the morbidity and mortality of cancer. There is, however, a heterogeneous response to the condition, according to the AT depot. As plasma leptin concentration has been often reported to vary in cachexia, we have measured (species specific radioimmunoassay) the local concentration of leptin in three AT depots: retroperitoneal (RPAT), epididymal (EAT) and mesenteric (MES) of Walker 256 tumour-bearing rats. A redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
1
33

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 65 publications
7
54
1
33
Order By: Relevance
“…While MEAT and RPAT mass decreased to the greatest extent, at least on day 14 (with no change in the intermediary stage of cachexia -day 7), the mass of EAT did not differ from control. This finding is in agreement with our previous study (Machado et al 2004) and we further demonstrate that reduction in WAT depot weight (absolute and relative) of Walker 256 tumour-bearing rats seems to occur only on the 14th day post-inoculation (after which animals spontaneously die due to cachexia). Adipocyte morphometrical data also changed in the late stage of cachexia, at which time cells from MEAT were found to be larger compared with day 0.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…While MEAT and RPAT mass decreased to the greatest extent, at least on day 14 (with no change in the intermediary stage of cachexia -day 7), the mass of EAT did not differ from control. This finding is in agreement with our previous study (Machado et al 2004) and we further demonstrate that reduction in WAT depot weight (absolute and relative) of Walker 256 tumour-bearing rats seems to occur only on the 14th day post-inoculation (after which animals spontaneously die due to cachexia). Adipocyte morphometrical data also changed in the late stage of cachexia, at which time cells from MEAT were found to be larger compared with day 0.…”
Section: Discussionsupporting
confidence: 94%
“…Cancer cachexia induces wasting of fat mass that accounts for a large part of the dramatic weight loss observed both in humans (Fouladiun et al 2005, Agustsson et al 2007, Dahlman et al 2010) and in animals (Machado et al 2004, Bing et al 2006, Asp et al 2010, and lipid metabolism is markedly altered (Seelaender et al 1996, Tisdale 2009, Arner 2011. Walker 256-induced cachexia was efficient at eliciting loss of body weight in terms of both absolute and relative weight (percentage of total body mass) of the fat depots, with consequent abnormalities in plasma biochemical profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different way, CD3 Ly positive cells were the main immune cells found in the fibrotic areas. We previously hypothesized that infiltrating ATMϕs may play an important role(s) in cachexia‐associated AT remodelling, based on our observation that ATMϕs in cachectic rats and humans are placed surrounding or in close proximity to the adipocytes 46. In addition, we demonstrated that ATMϕs aggregates display a CLS pattern.…”
Section: Discussionmentioning
confidence: 64%
“…Consequently, CLS become lipid‐laden ‘foam cells’47 frequently observed in AT in obesity. In an animal model of cachexia, we have shown46 that foam‐cell resembling macrophages are present in the AT. During CC, increased lipolysis has been consistently demonstrated in both patients7, 11 and animal models9, 32 and that might be an important source of lipids to ATMϕs.…”
Section: Discussionmentioning
confidence: 92%